Pathogenicity of Pasteurella multocida A:1 in experimentally infected chickens and chicken embryos - Shivchandra, S B; Kumar, A A; Singh, S D; Shivakumar, B M; Prasanna, K (The Indian Journal of Animal Sciences, 2005)
The pathogenicity of Pasteurella multocida A:1 was studied by experimentally infecting layer chickens and 11-day old embroynated chicken eggs. Acute clinical signs, mortality, general hyperaemia, mild to moderate degrees of congestion, haemorrhages and degenerative changes in visceral organs were noticed in infected birds. Mortality, severe congestion of embryos, haemorrhages, degenerative and vascular changes in liver, kidneys and heart were observed following inoculation of embryonated chicken eggs by chorio-allantoic membrane (CAM) route.